3D printing: the new industrial revolution - Velasco, Edwar Guillermo; Revelo, David Armando (I+ T+ C- Research, Technology and Science, 2019)
A historical overview is presented, as well as some basic operating principles about one of the most important disruptive technologies of the 20th century: 3D printing. Despite the fact that the concept of 3D printing has been widely spread, there is a part of the population that does not know the fundamentals and scope of this disruptive technology. This work shows a reflection about the current state of technology and its impact on different industries, and the development of an exelearning educational resource is proposed as a tool for appropriation of technology. 3D digitization has been known since the 20th century; Nowadays it can enter new fields, from the academy, through the numerous applications in the market and industry, even in the social area, offering almost infinite applications for materialize in new products. When talking about 3D printing, it is inferred that the process carried out is similar to paper printers, but instead of depositing ink, it is done with any other material that may be of a different nature to achieve a three-dimensional object. 3D printing uses only the material needed to make objects, minimizing waste of supplies. In contrast, conventional manufacturing methods manufacture parts with considerable material losses. 3D printing technologies are changing the world and industrial processes because they allow to obtain results quickly, effectively and accurately in relation with the manufacturing of objects from digital designs. These types of technologies are applicable in different disciplines, the literature review showed that there are important advances in industries such as: construction, automotive, aerospace, medical, transportation, food, and education. However, there are still several challenges to be addressed about synthesis of materials with adequate mechanical characteristics.